Source apportionment and quantification of liquid and headspace leaks from closed system drug-transfer devices via Selected Ion Flow Tube Mass Spectrometry (SIFT-MS) - Amos Doepke (Public Library of Science (PLoS), 2021)
A system to differentiate and quantify liquid and headspace vapor leaks from closed system drug-transfer devices (CSTDs) is presented. CSTDs are designed to reduce or eliminate hazardous drug (HD) exposure risk when compounding and administering HDs. CSTDs may leak liquid, headspace, or a mixture of the two. The amount of HD contained in liquid and headspace leaks may be substantially different. Use of a test solution containing two VOCs with differences in ratios of VOC concentrations in the headspace and liquid enables source apportionment of leaked material. SIFT-MS was used to detect VOCs from liquid and headspace leaks in the vapor phase. Included in this report is a novel method to determine the origin and magnitude of leaks from CSTDs. A limit of leak detection of 24 μL of headspace vapor and 0.14 μL of test liquid were found using Selected Ion Flow Tube Mass Spectrometry (SIFT-MS).